2022
DOI: 10.7759/cureus.20964
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the First 100 Cases of Laparoscopic Nephrectomy: A Single-Center Experience

Abstract: Since 1990, when the first laparoscopic nephrectomy was performed, there has been a dramatic increase in interest in laparoscopic procedures in urological surgeries. The aim of the study was to present our experience with the first 100 cases of laparoscopic nephrectomy at our institute, identify the difficulties encountered, and discuss how to approach the solutions. Materials and methodsThe data of all patients who underwent laparoscopic nephrectomy between May 2017 and April 2019 (n=100) were reviewed retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Thirty-two percent of their cases had a prior history of abdominal surgery, such as appendectomy, C-section, or pyelolithotomy. 14 In the present study, 51.48% had laparoscopic nephrectomy on the right side and eighteen percent of the patients had a previous surgical history on the ipsilateral side.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…Thirty-two percent of their cases had a prior history of abdominal surgery, such as appendectomy, C-section, or pyelolithotomy. 14 In the present study, 51.48% had laparoscopic nephrectomy on the right side and eighteen percent of the patients had a previous surgical history on the ipsilateral side.…”
Section: Discussionmentioning
confidence: 48%
“…Mithani et al had Very few complications; one percent of wound infections, one percent of prolonged ileus, while two percent cases required blood transfusion. 14 Similarly, Quddus et al reported majority complications being Clavien Grade-2 including 10% blood transfusion. 15 We categorized complications based on Clavien-Dindo classification: Grade 1 (n=3; 2.97%), Grade-2 (n=6; 5.94%), Grade-3A (n=1; 0.99%), and grade 3B (n=1; 0.99%) complications were observed ( Table-II ).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations